Measures of Adherence and Challenges in Using Glucometer Data in Youth with Type 1 Diabetes: Rethinking the Value of Self-Report. (21st December 2017) - Datye, Karishma A.; Patel, Niral J.; Jaser, Sarah S.
Abstract : Purpose . The current study compares the relative strength of associations of different adherence measures with glycemic control in adolescents with type 1 diabetes, while highlighting the challenges in using more objective measures (i.e., glucometer data). Methods . Adolescents with type 1 diabetes (n = 149 ) and their caregivers completed a questionnaire measure assessing adolescents' adherence (Self-Care Inventory (SCI)) to the diabetes regimen. Adolescents' glucometers were downloaded to determine average blood glucose checks per day, as an objective measure of adherence. A measure of glycemic control (hemoglobin A1c (HbA1c)) was obtained as part of adolescents' regular clinic visits. Results . Adolescents' self-reported adherence to the treatment regimen was more strongly correlated with HbA1c than caregivers' reports of adherence. In multivariate analyses, both adolescents' self-report of adherence and average blood glucose checks per day (obtained via a glucometer) were significant predictors of HbA1c. Challenges to obtaining glucometer data were identified. Conclusions . The findings highlight adolescents' self-report of adherence using the SCI as a brief and meaningful measure to understand and improve adolescents' glycemic control, particularly when glucometer data is difficult to obtain.